Productivity and technical efficiency of smallhold hog farming from the 3rd district of Pampanga, the Philippines - Salazar, Joel R. (The Philippine Journal of Veterinary Medicine, 2022)
This study aimed to determine and identify the productivity and technical efficiency of smallhold hog farms in the 3rd District of Pampanga, the Philippines. This study also recommended specific production inputs and technical parameter/s that can demonstrate improvement in reproductive efficiency and using a sow productivity index equation. Maximum likelihood estimates (MLE) were used and analyzed through Stochastic Production Frontier Approach. All variables for pig production were estimated to different functional forms and were all transformed to their natural logarithm, squared terms, and interaction terms. The most influential input variables are in sows (0.401) and in piglets born alive (0.52), which can increase their level of productivity as demonstrated by a positive and significant influence at p< 0.05 and p < 0.01 level of significance in the production output, respectively. It was also revealed that variables in the inefficiency model were efficient indicators with a significant effect on technical efficiency and with the inclusion of 21-day litter weight, can generate a Sow Productivity Index (SPI) based on the stochastic production frontier estimation of the relevant reproduction efficiency parameters. The high level of mean technical efficiency at 92% demonstrated that only 8% is needed for improvement for technical-based reproductive efficiency parameters.